Statement by the Managing Director to the International Monetary and Financial Committee on the Global Economy and Financial Markets. (Policy Papers; Policy Paper ;, 2011)
The recovery is solidifying. However, old policy challenges still need to be fully addressed and new challenges are arising, especially on account of rising commodities prices. In many advanced economies the handoff from public to private demand is proceeding. But unemployment remains high and weak public balance sheets and still vulnerable financial sectors mean that the recovery is subject to downside risks. In many emerging market economies, overheating and financial imbalances present growing policy concerns. Monetary policy should stay accommodative in advanced economies, but needs further tightening in a number of emerging and developing economies to rein in inflationary pressure and rapid credit growth. Additionally, in emerging surplus economies, real exchange rate appreciation is needed to help contain inflation and support global demand rebalancing. In most economies, the time has come to begin fiscal adjustment by implementing measures to steadily reduce debt ratios toward more prudent levels. Moreover, financial sector repair and reform need to accelerate. Absent major progress on all these fronts, the recovery will remain vulnerable and job creation will continue to fall short of requirements in many parts of the world.